Moral Economies of Corruption : State Formation and Political Culture in Nigeria - Pierce, Steven, 1968- (Book collections on Project MUSE., 2016)
Nigeria is famous for "419" emails asking recipients for bank account information and for scandals involving the disappearance of billions of dollars from government coffers. Corruption permeates even minor official interactions, from traffic control to university admissions. In Moral Economies of Corruption Steven Pierce provides a cultural history of the last 150 years of corruption in Nigeria as a case study for considering how corruption plays an important role in the processes of political change in all states. He suggests that corruption is best understood in Nigeria, as well as in all other nations, as a culturally contingent set of political discourses and historically embedded practices. The best solution to combatting Nigerian government corruption, Pierce contends, is not through attempts to prevent officials from diverting public revenue to self-interested ends, but to ask how public ends can be served by accommodating Nigeria's history of patronage as a fundamental political principle.